The c-Myc target gene PRDX3 is required for mitochondrial homeostasis and neoplastic transformation - Wonsey, Diane R. (The National Academy of Sciences, 2002)
Deregulated expression of the c-Myc transcription factor is found in a wide variety of human tumors. Because of this significant role in oncogenesis, considerable effort has been devoted to elucidating the molecular program initiated by deregulated c-myc expression. The primary transforming activity of Myc is thought to arise through transcriptional regulation of numerous target genes. Thus far, Myc target genes involved in mitochondrial function have not been characterized in depth. Here, we describe a nuclear c-Myc target gene, PRDX3, which encodes a mitochondrial protein of the peroxiredoxin gene family. Expression of PRDX3 is induced by the mycER system and is reduced in c-myc(−/−) cells. Chromatin immunoprecipitation analysis spanning the entire PRDX3 genomic sequence reveals that Myc binds preferentially to a 930-bp region surrounding exon 1. We show that PRDX3 is required for Myc-mediated proliferation, transformation, and apoptosis after glucose withdrawal. Results using mitochondria-specific fluorescent probes demonstrate that PRDX3 is essential for maintaining mitochondrial mass and membrane potential in transformed rat and human cells. These data provide evidence that PRDX3 is a c-Myc target gene that is required to maintain normal mitochondrial function.